Krzesiny i Kreising – między pamiętaniem a pomijaniem. Polskie miasteczko wobec historii, pamięci i rywalizacji w cierpieniu - Matijevic, Danijel; Kwiatkowski, Jan (Zagłada Żydów. Studia i Materiały, 2014)
The area around Krzesiny, located near the city of Poznań, Poland, witnessed several dark events during World War II: Germans oppressed the local population, culminating in a terrorizing action dubbed “akcja krzesińska;” also, a forced labor camp, named “Kreising,” was built near the township, housing mainly Jews. After the war, the suffering in Krzesiny was remembered, but selectively – “akcja” and other forms of Polish suffering were commemorated, while the camp was not. By exploring the “lieux de mémoire” in Krzesiny – dynamics of memory in a small township in Poland – this paper uses localized research to address the issue of gaps in collective memory and commemoration. We briefly look at the relevant history, Polish memory regarding wartime events in Krzesiny, and the postwar dynamics of collective memory. Discussing the latter, we identify a new phenomenon at work, one which we dub “collective disregard” – group neglect of the past of the “Other” that occurs without clear intent. We argue that “collective disregard” is an issue that naturally occurs in the dynamics of memory. By making a deliberate investment in balanced remembrance and commemoration, societies can counter the tendencies of “disregard” and curb the controversies of competitive victimization claims, also called “competitive martyrdom”.